Nghiên cứu thành phần hóa học của quả cây giả bồ đông dương (Pseuduvaria indochinensis Merr.) - Minh Hằng, Nguyễn Thị; Giáp, Trần Hữu; Huệ, Cao Thị; Thành, Lê Nguyễn; Hùng, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
Polycerasoidol (1), N-heptacosanoyltryptamine (2), 1,2,4,5-cyclohexanetetrol (3), liriodenin (4) together with β-sitosterol (5) were isolated from the fruits of Pseuduvaria indochinensis. Their structures were identified by means of spectroscopic methods such as 1D and 2D NMR, MS. Three compounds 1, 3 and 4 have been isolated from Pseuduvaria genus for the first time. Keywords: Pseuduvaria indochinensis, polycerasoidol, liriodenin, 1,2,4,5-cyclohexanetetrol, N-heptacosanoyltryptamine.